(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: Employee engagement is one of the most recent areas of research in management. It is the basis for any organization’s success. The engaged workforce shows its physical and mental commitment, generates energy on the roles to be performed, and gives productivity to a maximum extent which helps in achieving overall business goals. Objective: The major objective of this study was to determine the level of employee engagement of the operational staff. Methodology: The questionnaire was prepared to test the knowledge, employee engagement levels, and organizational culture levels of the employees. Responses were recorded via the online medium from 100 samples (50 males and 50 females), the majority of them were in the age group of 20 to 25 years and were operational employees of 5-star hotels in Kolkata. A 5-point Likert scale was used. Result: The average knowledge score of the sample was 5.45, which indicated great awareness of the concept. The sample achieved an average score of 39.92 in employee engagement, 24.2 in job involvement, 40.59 in empowerment, and 24.78 in cognition, all of which were in the ‘high’ range. The average organizational culture score achieved by the sample was 89.57. Pearson’s correlation coefficient was calculated for the two variables, employee engagement, and organizational culture, and the correlation coefficient was, 0.534 among males and 0.569 among females. The values of the correlation coefficient indicated a positive correlation among the variables. Conclusion: The findings of this study contributed to the knowledge and understanding of the selected factors, which leads to a better understanding of organizational practices that will lead to employee engagement.